Electrical transport and optical properties of an organic semiconductor based on phthalocyanine - Yakuphanoğlu, Fahrettin; Kandaz, M.; Yarasir, M. N.; Senkal, F. B. (Elsevier Science Bv, 2007)
Electrical conductivity, thermoelectric power and refractive index disperson properties of the Co(II) complex of tetrasubstituted thiophene-attached phthalocyanine have been investigated for the first time. The electrical conductivity of the sample increases with increase in temperature. Electrical conductivity and thermoelectric power results suggest that the 2, 9, 16, 23-tetrakis-6-(-thiophene-2carboxylate)-hexylthio-phthlocyaninato cobalt (II) complex {M[Pc(S(CH2)(6)OCOC4H3S)(4)]; {M = Co (II)} (CoPc) sample is a p-type organic semiconductor. The electrical conductivity mechanism changes from thermally activated conductivity to the conductivity by hopping in the localized states. The refractive index at infinite wavelength and optical band gap of the CoPc sample were found to be 3.43 and 3.65 eV, respectively. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: phthalocyanine; thermoelectric power; organic semiconductor